A multi-echelon supply chain of deteriorating items with stock- and price-sensitive demand under consignment stock policy. Issue 3 (4th March 2023) - Hemmati, M.; Fatemi Ghomi, S. M. T.; Sajadieh, Mohsen S.
Abstract : This article proposes a coordinated inventory model for a deteriorating item. The buyer side consists of the warehouse and shelf, and items deteriorate in both levels of the buyer's stocking points. For the first time, this article develops a multi-echelon deteriorating model under vendor-managed inventory with consignment stock where the demand depends on stock and price. Although considering multi-echelon deterioration makes the mathematical model complicated, a heuristic algorithm is developed to obtain the optimal values of the delivered batches at each echelon and price to maximize the total profit. Analysis shows that two-echelon deterioration does not significantly affect price, but does affect the number of displayed items. When items deteriorate at the buyer's warehouse and shelf, the shelf size should be larger than the situation in which items only deteriorate on the shelf. Furthermore, the number of shipments at both buyer and vendor levels decreases as the deterioration rate increases.